2001
DOI: 10.1037/1040-3590.13.4.452
|View full text |Cite
|
Sign up to set email alerts
|

The Rorschach: Facts, fictions, and future.

Abstract: A large body of empirical evidence supports the reliability, validity, and utility of the Rorschach. This same evidence reveals that the recent criticisms of the Rorschach are largely without merit. This article systematically addresses several significant Rorschach components: interrater and temporal consistency reliability, normative data and diversity, methodological issues, specific applications in the evaluation of thought disorder and suicide, meta-analyses, incremental validity, clinician judgment, patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 150 publications
2
109
0
5
Order By: Relevance
“…For assessment science, awareness of these methodological similarities and differences facilitates an enhanced understanding of the tools available for measuring personality and cognition, with recognition that the Rorschach task falls in a zone between the other two methods, providing a range of scores that span the continuum from what can be considered personality trait and state variables to what can be considered cognitive and information processing variables. With its international foundation, minimal effects from demographic variables, broad coverage of psychological dimensions, applicability to all but the youngest children, incremental validity relative to self-report methods Mihura et al, 2013;Viglione & Hilsenroth, 2001), the Rorschach continues to meet many clinical assessment needs across cultures. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For assessment science, awareness of these methodological similarities and differences facilitates an enhanced understanding of the tools available for measuring personality and cognition, with recognition that the Rorschach task falls in a zone between the other two methods, providing a range of scores that span the continuum from what can be considered personality trait and state variables to what can be considered cognitive and information processing variables. With its international foundation, minimal effects from demographic variables, broad coverage of psychological dimensions, applicability to all but the youngest children, incremental validity relative to self-report methods Mihura et al, 2013;Viglione & Hilsenroth, 2001), the Rorschach continues to meet many clinical assessment needs across cultures. .…”
Section: Discussionmentioning
confidence: 99%
“…Rorschach normative samples has revealed that the CS norms used at that time were the problem rather than cultural differences, as even nonpatients from majority culture deviated in similar ways from the CS norms Meyer, Shaffer, Erdberg, & Horn, 2014;Meyer, Viglione & Giromini, 2014a;Viglione & Hilsenroth, 2001;Viglione & Meyer, 2008).…”
Section: Rorschach Scores and Ethnicitymentioning
confidence: 99%
“…There are meta-analytic studies (Atkinson, Quarrington, Alp, & Cyr, 1986;Bornstein, 1999;Hiller, Rosenthal, Bornstein, Berry, & Brunell-Neulib, 1999;Parker, Hanson, & Hunsley, 1988), which are regarded as supporting the validity of the Rorschach. However, these studies have been criticised as being methodologically defective, and several researchers have engaged themselves in a controversy concerning the value of the analyses Garb, Florio, & Grove, 1998Hunsley & Bailey, 1999;Lilienfeld et al, 2000;Meyer & Archer, 2001;Parker, Hunsley, & Hanson, 1999;Rosenthal, Hiller, Bornstein, Berry, & Brunell-Neulieb, 2001;Viglione & Hilsenroth, 2001;Weiner, 2001).…”
Section: The Rorschach Controversymentioning
confidence: 99%
“…Proponents and critics of the CS have also debated the temporal consistency and the interrater reliability of the CS (Acklin, McDowell, Verschell, & Chan, 2000;Costello, 1999;Ganellen, 2001;Garb et al, 2001;Hibbard, 2003;Hunsley & Bailey, 1999;Lilienfeld et al, 2000;McDowell & Acklin, 1996;Meyer, 1997aMeyer, , 1997bMeyer et al, 2002;Viglione, 1999;Viglione & Hilsenroth, 2001;Weiner, 2001;Wood, Lilienfeld, Nezworski, & Garb, 2001;Wood, Nezworski, & Stejskal, 1996a, 1996bWood, Nezworski, & Stejskal, 1997). In research, the reliability of the CS variables is now mostly calculated by using the intraclass correlation coefficient, ICC, as recommended by among others Acklin et al (2000).…”
Section: The Rorschach Controversymentioning
confidence: 99%
“…At the end of the 1990s, some published papers, such as those of Erdberg and Shaffer (1999) or Shaffer, Erdberg, and Haroian (1999) showed results that departed from Exner's on FQ, the crucial variable of interest here. That fact is well illustrated in a review by Viglione and Hilsenroth (2001), who showed the mean X+% was lower and the mean X-% and Xu% was higher in U.S. nonpatient samples when compared to Comprehensive System normative values. Exner's (2005) own new normative data show similar changes in the mean of FQ values.…”
mentioning
confidence: 69%